Ответы и объяснения

Лучший Ответ!
2014-03-16T11:23:41+04:00
2014-03-16T11:28:34+04:00
A/a^-b^: a/ab-a^=a/a^-b^*ab-a^/a=ab-a^/a^-b^=a*(b-a)/(a-b)(a+b)=-a*(a-b)/(a+b)(a-b)=-a/a+b=-0,7/0,7-2,1=-0,7/-0,14=0,7/0,14=1/2=0,5                    ответ:0,5                                                                (a-3)^-a*(5a-6)=a^-6a+9-5a^+6a=-4a^+9=-4*(-1/2)^+9=-4*1/4+9=-1+9=8   ответ:8                                                                
давай попробуем
http://znanija.com/task/5438682
НЕОТКРЫВАЕТСЯ
что?